Gauging the current status of natural history collections in Malaysia - Sapaat, Arney; Mohamed, Maryati; Dalimin, Mohd Noh (2019)
This study was carried out to gauge the current status of natural history collection centres in Malaysia, primarily focused on animal collections. Part of the research is reported here and it constituted objective one which is to compare the status of natural history collection between the various centres in Malaysia and also with three selected Southeast Asian tropical region museums in trying to understand need of the Malaysian public for a natural history museum. It maps out the locations, describes the number and kinds of specimens kept at each collection centre. Financial and governance aspects are also described. In total 11 centres were visited all over Malaysia. These collection centres and museums were managed by federal or state government or universities. Duration of visit at each location ranged from one to seven days. During the visit interviews were carried out with collection manager to obtained Questionnaire was also left behind for managers of centre to fill in and sent back to researchers. In addition, three natural history collection centres and museums in South East Asia tropical region were also visited: Bogor Zoological Museum, Indonesia; Lee Kong Chian Natural History Museum, Singapore and Mahachakri Sirindhorn Natural History Museum, Prince of Songkhla University, Thailand. Following the same protocol as with Malaysian centres, the information obtained enable researcher to make comparison between Malaysia and those in the region. This paper found that most of the natural history museums and collection centres were focused in the centre of peninsular Malaysia. However, natural history collections in Malaysia are still limited by state and national borders. Coordination and integration of these centres, currently runned separately by the federal, state governments, research institutions and institution of higher learning, is seen as the way forward to provide for a strong basis of understanding biodiversity among the Malaysian public.